Granulocyte-macrophage colony-stimulating factor increases tumor growth and angiogenesis directly by promoting endothelial cell function and indirectly by enhancing the mobilization and recruitment of proangiogenic granulocytes. Issue 2 (February 2017) - Zheng, Qiaowei; Li, Xueqian; Cheng, Xiaoliang; Cui, Ting; Zhuo, Yingcheng; Ma, Wenbin; Zhao, Xue; Zhao, Peipei; Liu, Xuanlin; Feng, Weiyi
Granulocyte-macrophage colony-stimulating factor has been widely used as an adjuvant therapy for cancer patients exhibiting myelosuppression induced by chemotherapy or radiotherapy. However, the effects of granulocyte-macrophage colony-stimulating factor on tumor growth, as well as its precise mechanism, are still controversial due to inconsistent evidence. This study investigated the effect of exogenous granulocyte-macrophage colony-stimulating factor on the growth of B16 melanoma, S180 sarcoma, and U14 cervical carcinoma in mice. The angiogenesis and recruitment of bone-marrow-derived cells were analyzed in tumor tissues. Interactions among granulocyte-macrophage colony-stimulating factor, bone-marrow-derived cells, and B16 tumor cells were investigated in vitro. Proangiogenic types of bone-marrow-derived cells in blood were assessed both in vivo and in vitro. The results showed that granulocyte-macrophage colony-stimulating factor markedly facilitated the growth of B16 and S180 tumors, but not U14 tumors. Granulocyte-macrophage colony-stimulating factor increased the densities of blood vessels and the number of bone-marrow-derived cells in B16 tumor tissues. The granulocyte-macrophage colony-stimulating factor–induced enhancement of tumor cell proliferation was mediated by bone-marrow-derived cells in vitro. Meanwhile, a distinct synergistic effect on endothelial cell function between granulocyte-macrophage colony-stimulating factor and bone-marrow-derived cells was observed. After separating two types of bone-marrow-derived cells, granulocyte-macrophage colony-stimulating factor–induced enhancement of tumor growth and angiogenesis in vivo was mediated by proangiogenic cells in granulocytes, but not monocytes, with CD11b +, vascular endothelial growth factor receptor 2, and C-X-C chemokine receptor 4 granulocytes possibly involved. These data suggest that granulocyte-macrophage colony-stimulating factor contributes to the growth and angiogenesis of certain types of tumor, and these mechanisms are probably mediated by proangiogenic cells in granulocytes. Applying granulocyte-macrophage colony-stimulating factor may attenuate the antitumor effects of chemotherapy and radiotherapy in certain types of tumor.